'Teucrium elymaiticum' (Lamiaceae): a new species for Flora of Iran - Attar, Farideh; Sotoodeh, Arash; Mirtadzadini, Mansour (Mediterranean Botany, 2019)
A new endemic species from western Iran, Teucrium elymaiticum Attar, Sotoodeh & Mirtadzadini, spec. nova is described. It belongs to section Scordium. Considering the combination of some characteristics like indumentum, bracts, pedicel, calyx, corolla size, and nutlet shape and size, the new species is related to T. scordium subsp. scordioides (Schreb.) Arcang.. The differences between these two species are highlighted. Images, distribution map and an updated identification key for the genus are presented.